SELF-FORMATION OF PROTECTIVE OXIDE-FILMS AT DRY SLIDING MILD-STEEL SURFACES UNDER A MEDIUM VACUUM - KONG, HS; YOON, ES; KWON, OK (ELSEVIER SCIENCE SA LAUSANNE, 1995)
The friction and wear at dry sliding steel surfaces under different vacuum conditions have been investigated to understand the mechanisms of wear of mild steel in vacuum. For the test, a ball-on-disk type of wear-rig has been built and implemented, allowing control of sliding speed, load and vacuum. A theoretical analysis of frictional heating at sliding surfaces and an experimental analysis of the influence of oxidation wear under different vacuum conditions are described. Results show that, at a low sliding velocity, a low load and under a medium vacuum, effective, protective oxide films can be formed on the sliding surface in a friction process with a self-regulating way, which results in both very low coefficient of friction (about 0.3) and mild wear. It is found that significant reduction in friction and wear is caused by formation of thin layer of Fe3O4 steel oxides on the surface which are promoted by a high surface temperature and a high plastic deformation at the local surface area, and they are formed of the compaction of wear debris while supporting the bearing load and preventing the direct intermetallic contact on the surface. Oxide films under a high vacuum and at a high sliding velocity are found that they are ineffective to protect the surface against severe wear. Results suggest that there is a critical regime with contact conditions for producing effective, protective oxide films of mild steel.
Keywords: OXIDATIONAL WEAR; TEMPERATURES; FRICTION; ORIGINS; LOAD